The problem of ethnic history: theoretical-methodological views (on the example of the ethnic history of the corn seed) - Usmonov, Murtoz (The Lingua Spectrum, 2025)
This article examines the theoretical and methodological foundations of ethnic history, with a particular focus on the example of the ethnic history of the Qo‘ng‘irot tribe. It analyzes the theoretical approaches and methodological methods related to the origin, development, and identification of ethnic groups. The article demonstrates that the main theoretical perspectives, such as ethnic identification, ethnogenesis, and processes of ethnic development, as well as the methodological approaches used in research, are of significant importance for the study of ethnic history.